Is there any genetic variation among native mexican and argentinian populations of Dalbulus maidis (Hemiptera: Cicadellidae)?. - Palomera, Veronica (2012)
The corn leafhopper Dalbulus maidis (Delong & Wolcott) (Hemiptera: Cicadellidae) originated in Mexico, but is found from southeastern and southwestern USA to Argentina. Differences in reproductive and phenotypic traits between Mexican (native) and Argentinian (adventive) populations have been previously reported, but information on their genetic variation is currently unavailable. The objective was to investigate possible genetic variability among D. maidis populations collected in Mexico on maize and maize relatives (annual and perennial teosintes) and on maize in Argentina. A region of the mitochondrial gene coding for the cytochrome oxidase subunit I (mtCOI) and the ribosomal internal transcribed spacer (ITS2) were sequenced and analyzed. We developed the forward and reverse primers for the DNA amplification of COI in D. maidis (dalCOI). Twenty two and 17 sequences for dalCOI and ITS2, respectively, were generated and analyzed. No genetic variation among Mexican and Argentinian populations was found in the ribosomal region and low genetic variation was found in the mitochondrial region. These results could be explained by the short evolutionary time scale, since both maize and the corn leafhopper moved throughout the Americas only in the most recent millenia, or in part to the limited host range, and thus a limited change in the corn leafhopper associated bacteria.